Perancangan Sistem Informasi Presensi Siswa Berbasis WEB Di SMA Muhammadiyah Waingapu - Muhammad Iqraman Bahctiar; Yustina Rada; Murry Albert Agustin Lobo (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
In the current era of computers, technology and information systems have become common aspects of daily life. The evolution of information technology, particularly in the use of computers and the internet, is rapid among society. The presence of technology and information systems greatly aids individuals in disseminating and receiving information. Due to its rapid development, technology and information systems are not only a medium for obtaining information but can also be used as tools in the academic world. The attendance of students at SMA Muhammadiyah Waingapu is still done manually or written using paper/books, making it prone to damage and loss. The purpose of this research is to facilitate teachers in retrieving student data so that when teachers need to conduct grade meetings or promotion meetings, it will be easier to collect each student's attendance. This system is built using the extreme programming method with PHP, CSS, Xampp, and MySQL programming languages.